The application of universal jurisdiction to the Tibetan genocide case - Esteve Moltó, José Elías (Universidad Pedagógica y Tecnológica de Colombia, 2011)
In recent times, especially as a result of the Pinochet case, the diverse interpretation of the principle of universal jurisdiction has faced continuous confrontation, not only with the doctrine, but also with the Spanish courts. The judgment of the Constitutional Court on the Guatemala case seems to have settled this controversy to a certain extent by recognizing the competence of the Spanish jurisdiction to prosecute universal crimes.